Metode Pembelajaran Maharat al-Kalam untuk Meningkatkan Keterampilan Berbicara Mahasiswa pada Tingkat Pemula - Novira, Nuraeni (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2017)
The title of this research is â€œMahÄrat al-KalÄm learning method in improving beginner student speaking proficiencyâ€. This journal concludes two problem statements, namely 1) What is the importance of MahÄrat al-KalÄm Learning? 2) How is the process of MahÄrat al-KalÄm at the beginner level? The study of al KalÄm has been very critical at the present day since Arabic Language taught in many schools and universities, but most of the students are unable to speak properly. Therefore, it is necessary for the teacher or lecturer to concern with the accurate method and technique within the learning process. Method applied in this research is descriptive analysis by literature review on the books of prominent scholars in Arabic Language. This research is expected to provide new insight for the teachers and the lecturers in the learning process of al-KalÄm specifically for the beginners.